The PNAE (National School Feeding Program) activity system and its mediations - Alves Da Silva, Eliane; Pedrozo, Eugenio Avila; Nunes Da Silva, Tania (Frontiers in Environmental Science, 2023)
The National School Feeding Program (PNAE—Programa Nacional de Alimentação Escolar) is a Brazilian policy that attends to 44 billion students per year, distributed in 5,568 municipalities, providing school meals to public school students. Law No. 11,947 establishes a minimum percentage of 30% to purchase foodstuffs directly from family farming. In addition to the general rules, it is possible to create specific rules for the operationalization of the program; therefore, this paper aims to characterize the dynamic process of the relationships and actions of social agents involved through the Activity System generated by Law No. 11,947 of 2009 in the municipality of Porto Velho in the state of Rondônia, located in the western Amazon. As a theoretical framework, cultural-historical activity theory (CHAT) and mediated action theory (MAT) were used. To achieve the objective, qualitative research and abductive reasoning were adopted, using a unique and incorporated case study as a strategy. In all, 49 interviews were conducted and analyzed using content analysis. The extent of the influenced community and the different realities to which the actors are exposed were verified.